Ungkapan Bermakna Budaya Dalam Upacara Meminang Gadis Etnik Galela Di Kokota Jaya - Galela, Dolfina (Universitas Sam Ratulangi, 2017)
Language and culture have a very close relationship and can not be separated. Indonesia has a variety of very interesting customs, as well as ethnic Galela in Kokota Jaya, North Halmahera in North Maluku province has a variety diariskan customs of the ancestors. One was at the event to woo the girl who is a manifestation of cultural values in the society. In the event there is a form to woo this girl lingual and lexical meaning phrases that have cultural significance. There is also the cultural meanings of verbal and nonverbal expression. This research may be necessary for people to know clearly the meaning of expressions of both verbal and nonverbal ceremonial woo the girl. This study aims to identify and analyze the forms of expression of cultural meanings contained in verbal and nonverbal expression on her proposed marriage ceremony in Kokota Jaya ethnic Galela.Based on the results and discussion can be concluded that there is a form limgual and lexical meaning in the ceremony there was to woo the girl. And there is a meaningful verbal and nonverbal expressions of culture in a ceremony to woo the girl. It is recommended that conducted an exhaustive review of her proposed marriage ceremonies. For Galela ethnic communities in Kokota Jaya especially the younger generation is expected to begin to learn and understand the use of regional languages become heritage.Keywords: Expression, Cultural, and Galela Ethnic